Displacements of the surface of a piezoelectric half-space with functionally-graded coating and circle electrode on the surface - Volkov, Sergey Sergeyevich; Vasiliev, Andrey Sergeyevich; Aizikovich, Sergey Mikhaylovich (Computational Continuum Mechanics, 2023)
A mathematical model describing the deformation of a material caused by the reverse piezoelectric effect is proposed. The model is based on an axisymmetric problem of electroelasticity for a half-space with a functionally-graded coating. An electric potential difference is applied across a circle area on the surface (an electrode whose thickness and elastic properties are neglected) and an infinity boundary of the half-space. Arbitrary independent variation of all electroelastic properties in depth of the coating is considered. The coating is assumed to be perfectly bonded to the substrate. The problem is solved using the bilateral asymptotic method in an approximated analytical form effective for any value of the relative thickness of the coating. Approximated analytical expressions containing finite quadratures are obtained for the distribution of radial and normal displacements and electric potential on the surface under the electrode and outside of it. Numerical calculations are provided for the distribution of radial and normal displacements and electric potential for two typical examples of functionally-graded coatings in a wide range of relative thickness values of the coating. Convergence of the results to those for a homogeneous non-coated half-space is obtained for small and large values of the relative coating thickness. Special attention is paid to the comparison of the results with those for a non-coated half-space. The redistribution of the electromechanical characteristics caused by the presence of the coating is most noticeably observed near the boundary of the electrode especially for thin and intermediate thickness coatings (in comparison with the size of the electrode).
Keywords: electroelasticity; contact problems; piezoelectricity; coating; functionally-graded material; electrode